Phase transitions of light in a dye-filled microcavity: observations and simulations. Issue 1 (May 2021) - Nyman, R.A.; Dhar, H.S.; Rodrigues, J.D.; Mintert, F.
Abstract: Photon thermalisation and condensation in dye-filled microcavities is a growing area of scientific interest, at the intersection of photonics, quantum optics and statistical physics. We give here a short introduction to the topic, together with an explanation of some of our more important recent results. A key result across several projects is that we have a model based on a detailed physical description which has been used to accurately describe experimental observations. We present a new open-source package in Python called PyPBEC which implements this model. The aim is to enable the reader to readily simulate and explore the physics of photon condensates themselves, so this article also includes a working example code which can be downloaded from the GitHub repository.